The effectiveness of systematic tooth brushing program on oral health status among primary school students in Samchuk district Suphanburi province - ล้อมทอง วิยดา (Thai Dental Public Health Journal, 2016)
The aim of this non-randomized longitudinal study cohort design was to evaluate the effectiveness of systematic tooth brushing program on oral health status among primary school students in Samchuk district, Suphanburi province. The comparison of oral health status and behavior of students among 4 schools of systematic tooth brushing program (S-group) and 4 schools of non-systematic tooth brushing program (NS-group) was done by using oral health status data from sealant program, Yimsodsai Dek Thai Fundee project. Oral health data of first grade students in 2009 were used as a baseline data compared to oral health status of the same student when they were at sixth grade in 2014. Analysis was done by using Chi-square analysis and independent t-test at 95% CI. Result showed that there were no statistically differences in DMFT between S-group and NS-groups at the baseline. By follow until grade sixth, the DMFT was significantly lower in the S-group than NS- group (DMFT=0.23 and 0.74 respectively, p=0.03). The incremental DMFT was significantly increased in both groups (p=0.043 in S-group, p=0.003 in NS-group). Mean gingival index, tooth brushing habit and sugar consumption behaviors were not difference. In conclusion, although there were DMFT increments in both groups, the incremental DMFT in S-group was significantly less increased than in NS-group.